Perkembangan Legislasi Hukum Islam di Indonesia - Moh Hatta (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2008)
The inevitability of legislation and codification of Islamic law is at least because of three factors; internal dynamic within Islamic legal theories, the shift from traditional to modern society, and complexity of social relation in the society. Many have written about development of Islamic law in Indonesia, either as general surveys of case studies. While among the most discussed topics is religious court, few has been written about Islamic positive law in Indonesia from pre independence period up to contemporary state. Indeed, there were some writings on Islamic legislation in Indonesia but their nature was merely concise survey which described briefly about the emergence of new trend on development of Islamic law in Indonesia. This article explains the covering scope of Islamic legislation in Indonesia as well as its legal binding within the hierarchy of legal products in Indonesia. This article is a bibliographical research analyzing data and legal documents. In addition, since Islamic legislation occupies new phase connected to another, the historical approach is employed in tracing the actual feature of development of Islamic law in Indonesia. This writing is aimed at discovering the trend of development of Islamic law in Indonesia, especially in post-new order period. So, it will be useful in locating the position of Islamic law in Indonesia as well as in opening new discourses within the area of Islamic law which has been dominated by textual studies in many years